Co-creation in healthcare: framing the outcomes and their determinants. (23rd January 2023) - Fusco, Floriana; Marsilio, Marta; Guglielmetti, Chiara
Abstract : Purpose: Understanding the outcomes of co-creation (CC) in healthcare is increasingly gaining multidisciplinary scientific interest. Although more and more service management scholars have pointed out the benefits of cross-fertilization between the various research fields, the literature on this topic is still scattered and poorly integrated. This study aims to summarize and integrate multiple strands of extant knowledge CC by identifying the outcomes of health CC and the determinants of these outcomes and their relationships. Design/methodology/approach: A structured literature review was conducted per PRISMA guidelines. A total of 4, 189 records were retrieved from the six databases; 1, 983 articles were screened, with 161 included in the qualitative thematic analysis. Findings: This study advances a comprehensive framework for healthcare CC based on a thorough analysis of the outcomes and their determinants, that is, antecedents, management activities and institutional context. Extant research rarely evaluates outcomes from a multidimensional and systemic perspective. Less attention has been paid to the relationship among the CC process elements. Research limitations/implications: This study offers an agenda to guide future studies on healthcare CC. Highlighting some areas of integration among different disciplines further advances service literature. Practical implications: The framework offers an operational guide to better shape managerial endeavors to facilitate CC, provide direction and assess multiple outcomes. Originality/value: This is the first extensive attempt to synthesize and integrate multidisciplinary knowledge on CC outcomes in healthcare settings by adopting a systematic perspective on the overall process.